Analisis Studi Kelayakan Bisnis Badan Usaha Milik Desa Di Ombulodata: - Sukma; Zulkifli Bokiu; Victorson Taruh (Al-Buhuts, 2023)
The purpose of this study was to determine the feasibility of establishing a business selling and buying dry shelled corn and selling agricultural needs. This type of research is a descriptive quantitative method with data collection techniques using primary data and secondary data using observation and interview methods. The data analysis technique used in analyzing the data in this study is non-financial in terms of marketing in terms of marketing mix strategy including product, price, distribution, and promotion. Whereas in the financial or financial aspects, data analysis techniques will be used in the form of calculations using the Payback Period (PP), Net Present Value (NPV), Internal Rate of Return (IRR) and Profitability Index (PI) methods. Based on the analysis of the marketing and financial aspects of the buying and selling of corn and the business of selling agricultural needs, the optimistic, moderate and pessimistic versions are feasible to run